2012
DOI: 10.1128/jvi.00407-12
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and Structural Characterization of Great Salt Lake Bacteriophage CW02, a Member of the T7-Like Supergroup

Abstract: Halophage CW02 infects a Salinivibrio costicola-like bacterium, SA50, isolated from the Great Salt Lake. Following isolation, cultivation, and purification, CW02 was characterized by DNA sequencing, mass spectrometry, and electron microscopy. A conserved module of structural genes places CW02 in the T7 supergroup, members of which are found in diverse aquatic environments, including marine and freshwater ecosystems. CW02 has morphological similarities to viruses of the Podoviridae family. The structure of CW02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 57 publications
(98 reference statements)
0
24
0
Order By: Relevance
“…Although they have diverged to the point that they do not always have easily recognizably similar AA sequence similarities, very divergent tailed phage MCPs have been examined and found to have similar protein folds (Parent et al , 2012; Shen et al , 2012; Zhang et al , 2013; Rizzo et al , 2014; Grose et al , 2014 and references therein). Thus, although they are amazingly diverse, all tailed phage MCPs are almost certainly very ancient homologues.…”
Section: Resultsmentioning
confidence: 99%
“…Although they have diverged to the point that they do not always have easily recognizably similar AA sequence similarities, very divergent tailed phage MCPs have been examined and found to have similar protein folds (Parent et al , 2012; Shen et al , 2012; Zhang et al , 2013; Rizzo et al , 2014; Grose et al , 2014 and references therein). Thus, although they are amazingly diverse, all tailed phage MCPs are almost certainly very ancient homologues.…”
Section: Resultsmentioning
confidence: 99%
“…Only two other phages were found that could be considered to have shared a common ancestor end to end with intervening insertions and deletions. These were Pseudomonas phage PA11 (14) and Salinivibrio phage CW02 (15). The method was also used to explore the relationship of RIO-1 to the two marine phages SIO1 and VpV262, which are known to be organized similarly to each other but have greatly divergent replicative genes (8).…”
Section: Resultsmentioning
confidence: 99%
“…Its most closely related relatives are Pseudomonas phage PA11 (14) and Salinivibrio phage CW02 (15). It contains a suite of genes that have predicted activities related to synthesizing and breaking unusual peptide linkages, first discussed by Iyer et al (16) as possibly being involved in modifying cell wall metabolism, and that are more fully described here.…”
mentioning
confidence: 98%
“…The N-terminal domain (yellow), cross-linking arm (green), A domain (blue), and P domain (red) are shown. As in a previous study (47), only the A and P domains were used in the fitting into the Basilisk capsid density. Coordinates omitted from the CW02 fitting (yellow, green, light red, and light blue) are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…UCSF Chimera was also used to fit coordinates of the bacteriophage HK97 major capsid protein (46) into the Basilisk capsid density. Only the core of the HK97 protein was fitted (47). HK97 coordinates were first fit into the Tϭ9 capsid of halophilic bacteriophage NS01 (D. Eng, P. Shen, M. Domek, D. Belnap, unpublished results), and this fit was used as a starting point for the fit into the Basilisk structure.…”
mentioning
confidence: 99%